Πíστiς Xρiστoȗ - Dixon, Cameron (East Carolina University, 2020)
Paul is one of the most iconic and emblematic figures of the New Testament, thus having significant influence throughout the western world and beyond. Understanding the writings of Paul and their views of Christology and Soteriology is foundational to developing sound Christian doctrine. The notion of “salvation comes through faith in Christ,” is the basis upon which many Christian denominations build their soteriology. This concept is derived from the Greek phrase πíστiς Xρiστoȗ (pistis Christou) found three times in various Pauline writings. This Greek phrase is translated as either “faith in Christ” (the more familiar option) or “faithfulness of Christ” (which is understood in scholarly circles, but largely unreferenced in the sacred arena). The πíστiς Xρiστoȗ debate involves the investigation of Paul’s letters, but also provides implications about who Jesus was and the nature and extent of his significance. Paul uses πíστiς Xρiστoȗ in his discussion of Gentile justification with the various communities to which he writes. The implication of this translation choice has soteriological significance, and this issue is significant in scholarly debate because the interpretation of this phrase drastically impacts interpretation of the Pauline letters. The heart of the πíστiς Xρiστoȗ debate is a translation issue of the Greek genitive case ending of the proper noun Christou. The issue in the Pauline phrase is whether the phrase πíστiς Xρiστoȗ is to be read as a subjective genitive—“faith of Christ”, or as an objective genitive—“faith in Christ. This phrasing appears throughout Paul’s writings, including in Romans 3:22, Galatians 2:16, and Philippians 3:9. The translation of this phrase in large measure defines Pauline Christology and soteriology. This paper will prove that the proper way to translate πíστiς Xρiστoȗ in the Pauline writings is to use the subjective genitive, so the phrase would be translated “faithfulness of Jesus Christ.” However, this paper will display the duality of the genitive, and while this phrase more heavily refers to the faithfulness of Jesus Christ, the simultaneous indication of the human component of faith is not absent. In her article Another Look at Πίστις Χριστοῦ Morna D. Hooker states: “...it may well be that the answer to the question ‘Does this phrase refer to Christ’s faith or ours?’ may be ‘Both.’ Nevertheless, that faith/faithfulness is primarily that of Christ, and we share in it only because we are in him” (p.62).
Keywords: Πíστiς Xρiστoȗ, Paul, Faith